Evaluation of Ecosystem Services and Mangrove Management Based on the Blue Economy Approach of Untung Jawa Island - Aryo Sahid Sujiwo; Nurlaili Nurlaili (Jurnal Mandiri : Ilmu Pengetahuan, Seni, dan Teknologi, 2022)
Mangrove forests have a very important role for people's lives, especially for people who live in coastal areas, both from environmental, economic and social aspects. However, the economic potential of the ecosystem services provided by mangrove forests has not been comprehensively calculated. As a result, the economic potential of mangrove forests in an area is often calculated to be lower than the actual economic potential. The purpose of this research is to evaluate the total economic potential of mangrove forest ecosystem services. The economic valuation method of ecosystem services used in this study is the Total Economic Value method, including the economic value of providing services, regulatory services, cultural services, and supporting services. The location of this research is on Untung Jawa Island, Seribu Islands, DKI Jakarta Province, while the research time is from July to September 2022. The data used in determining the economic value in this study are primary data and secondary data. The results of the analysis show that the total economic value of the provision of services is around IDR 607 million per year, support services around IDR 15 million per year, cultural services around IDR 1.3 billion per year, and regulatory services around IDR 34 billion per year. The findings of this study have implications that the government and related stakeholders are required to provide more intensive education to the public about the importance of sustainable management of mangrove forests for the development of a blue economy on the island.